The A6S Information Literacy Model for Digital Age Library instruction - Arman, Arman; Winarsih, Murni; Ibrahim, Nurdin (Universitas Malikussaleh, 2019)
Information literacy has became a central issue of modern society. The rapid growth of information technology (IL) and the emergence of new digital devices not only require changes in the concept of IL itself, but also in practice. This paper discusses findings of study of design and development research with the goal of study was to develop the development of blended model of information literacy instruction (ILI) for higher education library instruction. Data were collected through a checklist, pretest, posttest, and attitude questionnaire throughout a series of formative evaluation stages. The data obtained were analyzed qualitatively and quantitatively. The result showed that the A6S (analyze, select, search, sort, synthesize, share, and self-evaluation) information model effective to enhance students’ IL. offered recommendation regarding implementation in library instructions